Stratigraphic distribution and systematic composition of the Middle-Upper Devonian placoderms (anti-archs) from Central Kazakhstan - S. V. Moloshnikov (Известия высших учебных заведений: Геология и разведка)
The stratigraphie distribution and systematic composition of the Middle-Upper Devonian remains of antiarchs from the sediments of Central Kazakhstan are analyzed. Central Kazakhstan ichthyofauna contains mainly endemic taxons of antiarchs. The first remains of them appeared in this region at the Givetian. Pterichthyodids (Stegolepis, Sherbonaspis) and Dianolepidids (Tenizolepis) were widespread at that time. Bothriolepidids (Bothriolepis) and Asperaspidids (Asperaspis) also occured in the Givetian, but not so widely. Bothriolepidids (Bothriolepis) are only known antiarchs from the Frasnian and Famennian (Late Devonian), when the diversity of antiarchs decreased.